Determinants of audit fees: Auditor status, risk, report lag, and ownership structure - Kristiana, Stefanie; Carolina, Yenni (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This study aims to analyze the factors influencing audit fees in financial sector companies listed on the Indonesia Stock Exchange (IDX). The variables examined include audit firm status, company risk, audit report lag, and type of ownership. Methods – Secondary data were collected using a purposive sampling method from financial sector companies during the 2021–2023 period, resulting in 201 firm-year observations. The data were analyzed using multiple linear regression. Findings - The results indicate that all independent variables—audit firm status, company risk, audit report lag, and type of ownership—have a positive influence on audit fees. Implications - The findings contribute to auditors, regulators, and stakeholders by providing insights into the determinants of audit fees and emphasizing the importance of high-quality audits in maintaining financial transparency and accountability. Originality - This research offers novelty by highlights the role of ownership type, a variable that has received limited attention in prior studies, particularly within the context of Indonesia's financial sector.